Structural and Trap‐State Density Enhancement in Flash Infrared Annealed Perovskite Layers. Issue 14 (26th June 2021) - Brunova, Alica; Vegso, Karol; Nadazdy, Vojtech; Nadazdy, Peter; Subair, Riyas; Jergel, Matej; Majkova, Eva; Pandit, Pallavi; Roth, Stephan V.; Krasnansky, Alexander; Hinderhofer, Alexander; Schreiber, Frank; et al.
Abstract: Perovskite solar cells are well‐known for their high energy conversion efficiency, low‐temperature processing, and cost‐effective production. Flash infrared annealing (FIRA) of slot‐die cast perovskite precursors offers an attractive manufacturing route using high‐throughput roll‐to‐roll technology. Despite the recent progress in FIRA perovskite annealing, the optimal composition of the perovskite precursor is yet to be developed. Here, the effect of methylammonium chloride (MACl) on the perovskite structure and trap‐state density as a function of the FIRA annealing time is investigated. In situ real‐time grazing‐incidence wide‐angle X‐ray scattering (GIWAXS) is employed to monitor the perovskite layer formation during FIRA annealing with millisecond temporal resolution. In addition, the density of states in the bandgap is estimated using ex situ energy‐resolved electrochemical impedance spectroscopy. Evidence is found that adding 10% MACl into the perovskite precursor solution significantly improves the crystallographic orientation of the perovskite layers while reducing the trap‐state density by one order of magnitude. In addition, using time‐resolved GIWAXS, the most favorable time window for the FIRA processing of perovskite films with the lowest mosaicity and trap‐state density is identified. The results are of general importance for elucidating the appropriate temporal windows in complex and fast‐evolving crystallization processes. Abstract : Flash infrared annealing (FIRA) of slot‐die cast perovskite precursors offers an attractive fabrication route using high‐throughput roll‐to‐roll technology. In situ grazing‐incidence wide‐angle X‐ray scattering and ex situ energy‐resolved electrochemical impedance spectroscopy are used to identify the most favorable time window for FIRA processing of perovskite films with the lowest mosaicity and trap‐state density.